If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3h + 2) + -4h = 0 Reorder the terms: 2(2 + 3h) + -4h = 0 (2 * 2 + 3h * 2) + -4h = 0 (4 + 6h) + -4h = 0 Combine like terms: 6h + -4h = 2h 4 + 2h = 0 Solving 4 + 2h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2h = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2h = 0 + -4 2h = 0 + -4 Combine like terms: 0 + -4 = -4 2h = -4 Divide each side by '2'. h = -2 Simplifying h = -2
| 6h+16=4 | | 15=8-5+2x | | 4(r-9)=8r-32 | | 6x-3=5+4x | | 3x-7=x+21 | | 2(x-3)=1.5(x-4)+x | | 5(z-4)=4z-20 | | 8p=7p | | 0=120-4.9t^2 | | 4n+17+n-2=180 | | 5(9+6)=8p | | (x-16)/3=3x | | Y=6x-17 | | x^2+3x-2.5=0 | | -4x-5y=17 | | 180n-360=s | | x^3-x^2+8x+6=0 | | 3z^3-24z^2+36z=0 | | 6x+17-x=135 | | 12k+6.5=k+15 | | 2*t^2-12t+97=0 | | 12(2-4x)=20(1-2x)-15x+3 | | 12(2-4x)=20(1-2x)-15x+13 | | 9-8k=0 | | 6x-5+7x+3=180 | | (b-g)(b-g)=0 | | 6x+13=2x+11 | | 9a^2+30at+25t^2= | | 3(5-r)-(15-r)=17 | | 6t-12=2t+2 | | (8+x)(8+x)=0 | | 5(4x+7)=120 |